Computer-mediated and face-to-face peer feedback: student feedback and revision in EFL writing. Issue 9 (8th December 2022) - Pham, Ha Thi Phuong
Abstract: This study investigates how two feedback forms and sequences influence peer feedback and revision. The two feedback forms included: written asynchronous computer-mediated communication (hereafter WACMC) in Google Docs and traditional oral face-to-face interaction (hereafter OF2F). These two forms were used in two sequences: WACMC followed by OF2F (WACMC–OF2F) and OF2F followed by WACMC (OF2F–WACMC). Participants were twenty-six Vietnamese EFL students. After feedback training, students completed four writing tasks, provided feedback in pairs, and finally revised their work. This study employed a mixed-method approach. Written and oral feedback, student revision, as well as student interviews were collected, transcribed, coded, and analysed. Paired-samples t -tests and ANOVA tests were employed to compare student feedback and revision in the two forms and sequences. The findings showed that: (1) more revision-oriented comments were associated with the WACMC form and with the WACMC–OF2F sequence; (2) written comments had a higher uptake rate in both sequences; (3) global revisions were more often found in the WACMC–OF2F sequence; (4) while students perceived WACMC feedback in Google Docs as more helpful than OF2F feedback, most suggested using both feedback forms. Pedagogical implications for the L2 writing class will also be included.